The Mesozoic accretionary complex in Northeast China: Evidence for the accretion history of Paleo-Pacific subduction - Zhou, Jian-Bo; Li, Long (Journal of Asian earth sciences, 2017)
[Display omitted] •Jilin-Heilongjiang HP belt records the onset of Paleo-Pacific plate subduction at 210–180Ma.•Early Permian arc type igneous rocks were related to the Mongol-Okhotsk oceanic subduction.•Nadanhada Terrane formed between the 210Ma and 137Ma with the final accretion at 137–130Ma. The Mesozoic accretionary complex in Northeast China, which mainly consists of the Jilin-Heilongjiang high-pressure (HP) metamorphic belt and the Nadanhada accretionary complex, are the key area to understand the Paleo-Pacific subduction-accretion. The Jilin-Heilongjiang HP belt is a HP metamorphic zone between the Jiamusi and Songliao blocks and consists of the Heilongjiang blueschist belt and the Zhangguangcai Complex. Previously published and our new geochronological data indicate that the collision between the Jiamusi and Songliao blocks along the Jilin-Heilongjiang HP belt occurred between 210 and 180Ma, suggesting that the Jilin-Heilongjiang HP belt is an important unit for characterizing the geodynamic switch from the north-south closure of the Central Asian Orogenic Belt to the onset of westward accretion related to subduction of Paleo-Pacific plate in the Latest Triassic to Early Jurassic. Early Permian igneous rocks with arc affinity in the eastern margin of the Jiamusi Block are more likely related to the Mongol-Okhotsk subduction rather than the Paleo-Pacific subduction or the collision between the Jiamusi and Khanka blocks as previously considered. The Nadanhada accretionary complex lies to the east of the Jiamusi Block, and is composed of the Yuejinshan and Raohe complexes. Compilation of published geochronological data indicate that the Yuejinshan Complex was probably formed between 210Ma and 180Ma, similar to ages for the Jilin-Heilongjiang HP belt along the western margin of the Jiamusi-Khanka Block. The Raohe Complex was formed later in the Late Jurassic to Early Cretaceous (170–137Ma), likely more related to the subduction-accretion of Paleo-Pacific plate. The final accretion in the target area took place in the Early Cretaceous (137–130Ma).